Genetic diversity in working germplasm collection of kabuli chickpea (Cicer arietinum L.) - V. Jayalakshmi, S. Rama devi* and M. Mohammed Imran (Electronic Journal of Plant Breeding, 2022)
Genetic diversity was assessed in working germplasm collection comprising of 207 kabuli chickpea accessions for seven yield attributes. Wide genetic variation was seen in the kabuli germplasm for seven important yield and yield traits. Genetic diversity in the germplasm was evident in the form of 13 distinct clusters, out of which cluster I accommodated maximum number with 67 genotypes followed by cluster III with 62 genotypes. The diversity of the genotypes was mainly due to phenological traits days to 50 % flowering, which contributed 39.41 per cent to the total diversity followed by days to maturity (35.76 %). Variation is seed size (100- seed weight) contributed 14.29 per cent to the total diversity measured. The genotypes in cluster IX were the most divergent which was shown by their higher intra cluster distance (9.04) followed by the genotypes in cluster XII, VI and V. The diversity between cluster X and cluster VI was the highest as their inter cluster distance was the highest (27.25) followed by cluster XII and VI (26.05). Low inter cluster distance (3.86) was observed between clusters X and VII. The most promising and divergent kabuli germplasm lines LBeG 7, NBeG 855, ICCV 08313, ICCV 083308, ICC 15568 and NBeG 731 were identified for inclusion in hybridization for realizing desirable transgressive segregants.